Neuropsychological parameters in male offenders with substance use disorders - Hoffmann, Fabian; Völlm, Birgit (Frontiers in Psychiatry, 2024)
Introduction: The impact of cognitive functions on treatment outcomes in forensic psychiatric patients with substance use disorders is not well understood. This study investigates whether neuropsychological deficits, such as in attention, executive functions, and social-emotional cognition, are associated with impulsivity and criminal history. Methods: 109 male patients with substance use disorders at the Clinic for Forensic Psychiatry in Rostock were screened using inclusion and exclusion criteria, with 30 consenting to participate. The tests included the Cambridge Neuropsychological Test Automated Battery (CANTAB) to assess cognitive functions in the areas of attention, psychomotor speed, social and emotional perception, and executive functions, with a particular focus on decision making, planning and problem solving. The Barratt Impulsiveness Scale (BIS-11) was used to measure impulsiveness. Results: Participants displayed significantly higher impulsivity levels on the BIS-11 compared to the general population and showed marked deficits in attention, psychomotor speed, and executive functions. There was a minimal correlation between impulsivity and cognitive performance, suggesting that impulsivity does not directly predict cognitive impairments. Notably, extensive criminal histories correlated with poorer cognitive performance, particularly in tasks requiring planning and problem-solving. Discussion: We found mixed support for the hypothesized associations between neuropsychological functions and criminal histories among patients with substance use disorders. While tasks related to planning and sustained attention showed clearer links, broader cognitive functions displayed inconsistent correlations. These findings emphasize the complexity of the relationship between cognitive deficits, impulsivity, and criminal history, highlighting the necessity for tailored assessments and rehabilitation strategies to enhance outcomes. Future research should focus on larger, longitudinal studies to validate these findings and refine therapeutic approaches.